Countering Anthropocentric Perspective of Ecology with the Dictum of the Gita - Adhikari, Bam Dev (Literary Studies, 2021)
Human beings and the natural world have remained in constant collision with each other since the beginning of human civilization. The biosphere is shared by millions living beings including human beings. From the early days of human civilization, human beings kept themselves in the centre and developed an attitude of us and them, human beings us and the entire plants, animals and elements them. In Complete anthropocentric perspective of development of about ten thousand years, human beings never thought about the impacts upon the natural world and as a result the entire earth is in disfigured appearance now. In this essay, I have made an argument that only karma irrespective of the benefits can slow down or even reverse the conflict between human beings and the natural world.